Mediastinal liposarcoma of mixed type in childhood: A report of a case with unusual histologic features - Anand Rajan K; Subbarao Kiran; Agarwala Sandeep; Gupta Siddhartha (Wolters Kluwer Medknow Publications, 2010)
We hereby report the occurrence of mediastinal liposarcoma in a 11-year-old female child. Dyspnea and wheezing of long-standing duration were the presenting complaints and a preoperative biopsy failed to yield the diagnosis. Histologic examination revealed heterogeneous areas with well-differentiated liposarcoma-like areas, areas resembling myxoid liposarcoma, and areas of dedifferentiation. Osteosarcomatous foci and whorled areas reminiscent of meningioma were identified in the dedifferentiated areas. Liposarcomas in the mediastinum are extremely rare tumors of childhood and the present case showed unusual histologic features. Complete surgical excision with clear surgical margins remains the primary modality of treatment, although chemotherapy and radiotherapy have been tried.